Assessment of genetic variability, its heritable components and character association in yield and yield contributing traits in apricot (Prunus armeniaca) - SINGH, DINESH; KUMAR, K; CHAUHAN, NIRMLA; DOGRA, R K; VERMA, PRAMOD (The Indian Journal of Agricultural Sciences, 2018)
The nature and magnitude of genetic variability and correlation studies was assessed in 20 apricot (Prunus armeniaca L.) genotypes for fruit, yield and quality traits. The phenotypic and genotypic coefficients of variation were almost identical in expression for these traits. High heritability and high genetic gain were reported for fruit weight and yield per tree. High heritability with moderate genetic gain was obtained for titratable acidity, pulp/stone ratio, stone width, fruit breadth, firmness, fruit length, total sugars and TSS. Genotypic and phenotypic correlationsfor important component traits were also significant with each other. Maximum positive direct effect cited towards yield were contributed by fruit weight, followed by phenols, sugar/acid ratio, TSS, stone width, fruit breadth and non reducing sugars. Hence, selection can prove effective for improvement in fruit yield and other traits.